A proton-exchange poly(acrylic acid) supramolecular hydrogel for ultrahigh uranium adsorption. Issue 37 (10th September 2021) - Sun, Zhongkuan; Chen, Yongyi; Liu, Yan; Na, Bing; Meng, Cheng; Zhang, Shuang; Zou, Shufen; Liu, Hesheng
Abstract : A PAA supramolecular hydrogel, via hydrogen bonding interactions, is capable of proton-exchange with uranyl ions. High-density carboxyl groups and exchangeable protons in PAA chains enable an ultrahigh uranium uptake, e.g. 1362 mg g −1 in 20 mg L −1 uranium-spiked water. Abstract : The development of high-efficiency absorbents is an ongoing demand to purify uranium-containing wastewater. This study reports a poly(acrylic acid) (PAA) supramolecular hydrogel with hydrogen bonding interactions via physical cross-linking in acidic solutions. The protons in the carboxyl groups of the PAA hydrogel can exchange with uranyl ions in aqueous solution during adsorption, and vice versa upon desorption/regeneration. It enables easy uranyl coordination with the PAA hydrogel, responsible for an ultrahigh uranium uptake of 1362 mg g −1 in 20 mg L −1 uranium-spiked water (pH = 7). In addition, the PAA hydrogel can tolerate high-concentration metal cations to a large extent, beneficial for high-efficiency uranium removal under realistic conditions. The findings give deep insights into the development of high-efficiency adsorbents for uranium removal from wastewater via supramolecular tailoring.